Si Kenyal Manis, Obat Diabetes Mujarab - David Christian Ferdinand (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2019)
A serious disease occurs when the pancreas produce insufficient insulin is called diabetes. A various complications that affected to eyes, heart, and nervous system caused by diabetes. The use of synthetic drugs both oral and injection can cause a serious side effects like hypoglycemia. Based on these reasons, many researchers try to develop an anti-diabetic drugs derived from natural resources.One of the plants which potential to decrease glucose level in diabetic patients is Cinnamon (Cinnamomun zeylanicum). Cinnamon extract is very potent to decreases the glucose level in diabetic conditions. Based on this, the cinnamon extract will formulate in softgel forms. The manufacturing process occurs by encapsulate the extract with gelatin film as a shell material. Gelatin is a chewy shell material. The addition of plasticizer in gelatin is very important because its can affected to flexibility of capsule. The encapsulation process with rotary die method occurs using a special machine. The encapsulation process occurs by create a contract manufacture with third person. To ensure theproduct quality, a various test like organoleptic, weight-content uniformity, and rupture test was conducted.